Penegakan Hukum Tindak Pidana Terorisme Bom Bunuh Diri Berdasarkan Undang-Undang Nomor 05 Tahun 2018 Tentang Terorisme di Polrestabes Medan - Tomy Mangaratua Butar-butar; Ediwarman Ediwarman; Rizkan Zulyadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
With the formulation of the problem, namely (1) What is the form of prevention of criminal acts of terrorism according to the provisions of Law no. 05 of 2018 concerning terrorism, (2) What are the causes of terrorism at the Medan Polrestabes, (3) How is the law enforcement carried out by the Police related to the occurrence of terrorism at the Medan Polrestabes. This research method uses normative juridical research by analyzing laws and regulations and conceptual analysis with descriptive data analysis. The results of this study indicate that the prevention of criminal acts of terrorism conducted by the government is conducted through national preparedness, counter-radicalization, and deradicalization. The cause of the suicide bombing at Polrestabes Medan was the lack of vigilance by the police officers guarding the front post, leaving people who at that time wanted to take care of the SKCK free. Law enforcement conducted by the National Police regarding the occurrence of terrorism at the Medan Polrestabes can be seen from (a) Legal Substance, (b) Law Enforcement, (c) Facilities and Infrastructure, (d) Society, (e) Culture.